Patient survival following renal transplantation in Indigenous populations: A systematic review. Issue 1 (16th December 2019) - McGuire, Connor; Kannathasan, Sreedharan; Lowe, Matthew; Dow, Todd; Bezuhly, Michael
Abstract: Background: Inequities in health care predispose Indigenous populations to poor health outcomes. The objective of this study was to examine patient survival and other post‐transplant outcomes of kidney transplantation among Indigenous patients compared with non‐Indigenous populations. Methods: A systematic review of MEDLINE, EMBASE, and Google Scholar was undertaken from inception to September 30, 2019, using a computerized search. Publication descriptors and methodological and statistical details were extracted. Articles were assessed using the methodological index for non‐randomized studies (MINORS) scale. Results: Twelve studies were included. All studies were retrospective and published between 2004 and 2018. Mean Indigenous patient age was 40 (range: 8‐76), while non‐Indigenous was 41 (range: 6‐74). Mean sample size for Indigenous populations was 398 (range: 24‐1459), while for non‐Indigenous patients was 1102 (range: 53‐7555). Eight studies examined indigenous populations in Australia, two in Canada, one in the United States, and one in New Zealand. All studies were considered of high methodological quality and clinically homogenous. Results indicated that patient survival, graft survival, and delayed graft function were significantly reduced among Indigenous populations compared with non‐Indigenous populations. Conclusions: Post‐transplant outcomes among various Indigenous populations are significantly worse compared with non‐Indigenous populations. The reasons for poor outcomes are likely multifactorial. Improved standardized reporting of transplant outcomes of Indigenous patients is necessary to better inform healthcare services and improve clinical outcomes.